2007
DOI: 10.1111/j.1540-5915.2007.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Robust Resource Allocation Decisions in Resource‐Constrained Projects*

Abstract: The well-known deterministic resource-constrained project scheduling problem involves the determination of a predictive schedule (baseline schedule or pre-schedule) of the project activities that satisfies the finish-start precedence relations and the renewable resource constraints under the objective of minimizing the project duration. This baseline schedule serves as a baseline for the execution of the project. During execution, however, the project can be subject to several types of disruptions that may dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
0
43
0
2
Order By: Relevance
“…Resource assignment results can be found in Ait-Kadia, Menye and Kane (2011), Bachlaus, Tiwarib, andChan (2009), Celano, Costa, andFichera (2008), Eckstein and Rohleder (1998), Hwang and Kogan (2003) and Karsu and Azizoglu (2012). Resource-constrained project scheduling with a single type of resource can be found in Brucker and Kramer (1996), Chan, Wong, and Chan (2006), Debels and Vanhoucke (2007), Deblaere et al (2007), Herroelen (2011a, 2011b), Depuy and Whitehouse (2001), Klein (2000), Ranjbar, Reyck, and Kianfar (2009), Robinson and Moses (2006), Schirmer (2001), Tormos and Lova (2003), Vanhoucke, Demeulemeester, and Herroelen (2001b) and Van de Vonder et al (2006). Resource-constrained project scheduling with both renewable and non-renewable resources can be found in Bottcher et al (1999), Vanhoucke, Demeulemeester, and Herroelen (2001a), Lee and Lei (2001) and Nudtasomboon and Randhawa (1997).…”
Section: Introductionmentioning
confidence: 95%
“…Resource assignment results can be found in Ait-Kadia, Menye and Kane (2011), Bachlaus, Tiwarib, andChan (2009), Celano, Costa, andFichera (2008), Eckstein and Rohleder (1998), Hwang and Kogan (2003) and Karsu and Azizoglu (2012). Resource-constrained project scheduling with a single type of resource can be found in Brucker and Kramer (1996), Chan, Wong, and Chan (2006), Debels and Vanhoucke (2007), Deblaere et al (2007), Herroelen (2011a, 2011b), Depuy and Whitehouse (2001), Klein (2000), Ranjbar, Reyck, and Kianfar (2009), Robinson and Moses (2006), Schirmer (2001), Tormos and Lova (2003), Vanhoucke, Demeulemeester, and Herroelen (2001b) and Van de Vonder et al (2006). Resource-constrained project scheduling with both renewable and non-renewable resources can be found in Bottcher et al (1999), Vanhoucke, Demeulemeester, and Herroelen (2001a), Lee and Lei (2001) and Nudtasomboon and Randhawa (1997).…”
Section: Introductionmentioning
confidence: 95%
“…Different planning techniques have been studied, especially in analytical and simulation-based research (Kouvelis et al, 2005). Those streams of research have produced various sophisticated algorithms that enable the leveling and optimization of production plans (e.g., Davis and Mabert, 2000;Yang et al, 2002;Deblaere et al, 2007). However, empirical researchers have repeatedly observed that most practitioners use considerably less sophisticated planning methods than what is discussed in the academic literature (Melnyk et al, 1986;Wiers, 1997;McKay et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The project scheduling problem that we examine is discussed in [9, 21, 25, 30, 31, 37) and consists in the nonpreemptive scheduling of a set N = {0,1,…, n } of activities subject to a precedence relation A ⊂ N × N on a set K of renewable resource types with availability a k for type k ∈ K , where a precedence relation E is a a binary relation E ⊂ N × N that is irreflexive and transitive (i.e., a strict partial order on N ). Each activity i has a duration \documentclass{article} \usepackage{mathrsfs} \usepackage{amsmath, amssymb} \pagestyle{empty} \begin{document} \begin{align*}d_i\in \mathbb{N}\end{align*} \end{document} and occupies \documentclass{article} \usepackage{mathrsfs} \usepackage{amsmath, amssymb} \pagestyle{empty} \begin{document} \begin{align*}r_{ik}\in\mathbb{N}\end{align*} \end{document} units of resource type k during its execution.…”
Section: Definitions and Previous Resultsmentioning
confidence: 99%